Copper boosts the biostimulant activity of a vegetal-derived protein hydrolysate in basil: morpho-physiological and metabolomics insights - Rouphael, Youssef; Carillo, Petronia; Ciriello, Michele; Formisano, Luigi; El-Nakhel, Christophe; Ganugi, Paola; Fiorini, Andrea; Miras Moreno, Begoña; Zhang, Leilei; Cardarelli, Mariateresa; Lucini, Luigi; Colla, Giuseppe (Frontiers in Plant Science, 2023)
In addition to be used as a plant protection agent, copper (Cu) is also an essential micronutrient for plant growth and development. The bioavailability of Cu in agricultural systems can be limited due to its specific physical-chemical characteristics, leading to imbalances in plant production. To address this issue, an experimental trial was conducted on Genovese basil (Ocimum basilicum L.) in protected conditions to comparatively evaluate the effects of a vegetable protein hydrolysate (VPH), free Cu and Cu complexed with peptides and amino acids of vegetal origin (Cu and Cu-VPH, respectively), and a combination of VPH and Cu-VPH (VPH+Cu-VPH). The study showed that the combined application of VPH+Cu-VPH led to a significant average increase of 16.3% in fresh yield compared to the untreated Control and Cu treatment. This finding was supported by an improved photosynthetic performance in ACO2 (+29%) and Fv/Fm (+7%). Furthermore, mineral analysis using ICP OES demonstrated that Cu and Cu-VPH treatments determined, on average, a 15.1, 16.9- and 1.9-fold increase in Cu in plant tissues compared to control, VPH and VPH+Cu-VPH treatments, respectively. However, the VPH+Cu-VPH treatment induced the highest contents of the other analyzed ions, except for P. In particular Mg, Mn, Ca and Fe, which take part in the constitution of chlorophylls, water splitting system and photosynthetic electron transport chain, increased of 23%, 21%, 25% and 32% compared to respective controls. Indeed, this improved the photosynthetic efficiency and the carboxylation capacity of the plants, and consequently the physiological and productive performance of Genovese basil, compared to all other treatments and control. Consistently, the untargeted metabolomics also pointed out a distinctive modulation of phytochemical signatures as a function of the treatment. An accumulation of alkaloids, terpenoids, and phenylpropanoids was observed following Cu treatment, suggesting an oxidative imbalance upon metal exposure. On the contrary, a mitigation of oxidative stress was highlighted in Cu-VPH and VPH+Cu-VPH, where the treatments reduced stress-related metabolites. Overall, these results highlight an interaction between Cu and VPH, hence paving the way towards the combined use of Cu and biostimulants to optimize agronomic interventions.